Governing climate change: the impact of board attributes on climate change disclosure. (9th July 2019) - Ooi, Say Keat; Amran, Azlan; Yeap, Jasmine A.L.; Jaaffar, Amar Hisham
With its detrimental impacts, climate change is one of the most pressing challenges of human civilisation. To hold businesses accountable for climate change performance, corporate climate change disclosure has increased substantially over the last decade. Despite the importance of corporate governance, its impact on climate change disclosure remains under researched. Hence, this paper examines the impact of board attributes on climate change disclosure and attempts to explore the mediation effect of strategic corporate social responsibility (CSR) on such relationships. The results reveal that the extent of climate change disclosure increases with the presence of more female and independent directors. Enhanced insights into strategic CSR are expected to be valuable for board members seeking to internalise CSR strategically despite the insignificant indirect effect. Overall, these findings embrace worldwide initiatives to promote independence and gender diversity in the boardroom while demonstrating corporate transparency in climate change business impacts.